Reliability and validity of a new portable tethered sprint running test as a measure of maximal anaerobic performance - Limmer, M.; Berkholz, A.; de Marées, M.; Platen, P. (The Journal of Strength and Conditioning Research, 2020)
The purposes of this study were to develop a new portable tethered sprint running (PTSR) test for field-based anaerobic performance testing with restricted spatial conditions and the logistical challenge of carrying test equipment, and to determine reliability of the PTSR test. For validity, performance measures were compared with the cycle ergometer Wingate Anaerobic Test (WAnT) power outputs. Twelve recreationally active men and women (24.3 ± 1.6 years; 1.77 ± 0.07 m; 73.3 ± 12.5 kg) performed one familiarization trial followed by 3 randomly assigned experimental 60-second all-out effort trials consisting of one WAnT and 2 PTSR tests. All trials were performed in a randomized order on different days separated by at least 48 hours. Heart rate (HR) and maximum blood lactate concentration were recorded for each experimental trial to determine the physiological responses to the maximal efforts. Correlation coefficients indicated significant relationships between mean force (MF) and peak force (PF) in the PTSR test and mean power (MP) (r = 0.651, p = 0.022) and peak power (PP) (r = 0.877, p = 0.002) in the WAnT, but not for the fatigue index (r = 0.280, p = 0.379). In addition, both PTSR trials showed no significant differences (p > 0.05) between trials and a high reliability for the performance variables MF (intraclass correlation coefficient [ICC] = 0.98, coefficient of variation [%CV] = 7.7), PF (ICC = 0.98, %CV = 8.4), and HR (ICC = 0.92, %CV = 3.1). In conclusion, our results suggest that despite insufficient stimulation of anaerobic metabolism in some subjects resulting from poor implementation of test instructions, the PTSR is a reliable and valid test for an easy and practical assessment of maximal anaerobic performance under different field conditions.